Detecting pertussis in the Highlands region of Chiapas, Mexico - Jazmín Guadalupe Castañon-Ortíz; Héctor J Sánchez-Pérez; Mercedes Flores-López; Jorge León-Cortés; Adelina Schlie-Guzmán; Javier Gutiérrez-Jiménez; Jessica Lizzeth Gutiérrez-Ferman; Elvira Garza-González; Miguel Martín-Mateo; Natalia Romero-Sandoval; Allied Bencomo-Alerm; Anaximandro Gómez-Velasco (Instituto Nacional de Salud Pública, 2020)
Objective. To determine the rate of Bordetella pertussis infection in children admitted to a paediatric emergency hospital service. Material and methods. The positivity rate to B. pertussis infection was determined in 344 enrolled children under five-year old measured by culture, RT-PCR, clinical and laboratory predictors. Results. The positive rate of B. pertussis infection was 5.40% (95%CI=2.24-13.05) by culture, 16.12% (95%CI=2.42-29.84) by RT-PCR, and 36.66% (95%CI=18.36-54.97) by the laboratory predictor. Conclusions. Clinical and laboratory predictors represent a suitable tool to improve the diagnosis and prevention of pertussis by health services in the region of study.